The undamped and damped series elastic components of a vascular smooth muscle. - Mulvany, M J (1979)
Small arterial resistance vessels (internal diameter about 175 micrometer) have been mounted on a myograph that enabled their wall tension, T, and internal circumference, L, to be measured and controlled with a time resolution of about 4 ms. Maximally activated vessels were subjected to isometric releases (step changes in L) and isotonic releases (step changes in T) of varying extents and at two different temperatures (27 degree C and 37 degree C). The recovery from an isometric release was monotonic and did not include the two phases seen in skeletal muscles. The isotonic release response did, however, contain a velocity transient lasting about 150 ms: the velocity immediately after the release was about six times the steady shortening velocity. The form of both the isometric and isotonic release responses and their dependence on the extent of release can be explained in terms of a modified Hill model in which the "series elastic component" (SEC) is replaced by the series combination of an undamped-SED (that is, an undamped elastic element) and a damped-SEC (a Voigt element). Although the initial response to both types of release was independent of temperature, all stages of subsequent responses were temperature dependent, with Q10's in the range 1.5 - 2.0. The results suggest that the responses to isotonic and isometric releases may in part be due to active processes.